(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Scheduling is the process to minimize the schedule length by proper allocation of the tasks to the processors and arrangement of execution sequencing of the tasks. Multiprocessor Scheduling using Directed Acyclic Graph (DAG) is used in this research. Â An important implication of minimization of schedule length is that the system throughput is maximized. The objective of this survey is to describe various scheduling algorithms and their functionalities in a contrasting fashion as well as examine their relative merits in terms of performance and time-complexity. In this research, three BNP Scheduling Algorithms are considered namely HLFET Algorithm, MCP Algorithm and ETF Algorithm to calculate effective output by comparing the algorithms with eight test case scenarios with varying number of nodes and processors.